PENGARUH KARAKTERISTIK PEKERJAAN DAN IKLIM KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN OPERATOR BAGIAN TRIMMING I PT KRAMA YUDHA RATU MOTOR - Waspodo, Agung AWS; Anggraeni, Rianti (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
The purpose of the research are: 1) To know the description of job characteristics, communication climate, and job satisfaction employees at trimming 1 PT Krama Yudha Ratu Motor. 2) To know about the influence of job characteristics toward job satisfaction trimming 1 employee’s at PT Krama Yudha Ratu Motor. 3) To know about the influence of communication climate toward job satisfaction trimming 1 employee’s at PT Krama Yudha Ratu Motor. 4) To know about the influence of job characteristics and communication climate toward job satisfaction trimming 1 employee’s at PT Krama Yudha Ratu Motor. The analysis implemented in this research are descriptive and explanatory analysis. This research is taken 71 trimming 1 employee’s at PT Krama Yudha Ratu Motor. While data collection by using questionnaire and cultivated processed using SPSS 16. The result showed that: 1) Job characteristics has a significant influence on job satisfaction. 2) communication climate has a significant influence on job satisfaction. 3) job characteristics and communication climate has a significant influence on job satisfaction. Keywords: job characteristics, communication climate, job satisfaction